The Role of Individual and Organizational Expertise in the Adoption of New Practices - Greenwood, Brad N.; Agarwal, Ritu; Agarwal, Rajshree; Gopal, Anandasivam (Organization Science, 2019)
New information pertinent to organizational decision making, even when publicly available, may not diffuse rapidly in the form of adoption and transformation of organizational practices. In this study, we examine how different markers of expertise, each representative of human capital at both individual and organizational levels, moderates the speed of response to new information. We do so in the context of medical device utilization, viz. stents, for the treatment of stable coronary arterial disease by physicians practicing in hospitals. Results show that physicians possessing specialized expertise developed through deliberate practice adopt new guidelines significantly faster, as compared with physicians endowed with general expertise reflected in elite schooling or tenure. Furthermore, we observe significant spillovers within organizations from expertise gained through deliberate practice, indicating that physicians with expertise markers associated with deliberate practice are able to act as influential agents and help diffuse new practices within the organization. Our study thus extends the literature on both information diffusion and expertise by providing quantitative and qualitative evidence of the mechanisms at play in the adoption of new best practices. The online appendix is available at https://doi.org/10.1287/orsc.2018.1246 .